Compliance penal y su función en la atribución de responsabilidad penal / administrativa de las personas jurídicas - Sota Sánchez, Percy André (2018)
In this article, the author analyzes the nature of Compliance, achieving to formulate a concept based on its relationship with other business phenomena. Thereafter, he links Compliance with criminal and administrative responsibility of legal entities, analyzing the legislation of Peru, Chile, Spain and Italy, assigning them three functions: crime prevention, confirmation of the criminal law and formation of a compliance culture in the criminal law field.